Carbon Stored on Seagrass Community in Marine Nature Tourism Park of Kotania Bay, Western Seram, Indonesia - Mintje Wawo; Yusli Wardiatno; Luky Adrianto; Dietriech Geoffrey Bengen (Jurnal Manajemen Hutan Tropika, 2014)
Currently, the function of seagrass community as carbon storage has been discussed in line with “blue carbon” function of  that seagrass has. Seagrass bed are a very valuable coastal ecosystem, however, seagrass bed is threatened if compared to other coastal ecosystems, such as mangroves and coral reefs.  The threatened seagrass experienced also contributes to its capacity in absorbing CO2 emission from greenhouse gasses such as CO2 emission Temporal estimation  shows that CO2 emission will increase in the coming decade. On the other side, efforts to decrease climate change  can be influenced  by the  existence of seagrass.  Informations about existence of seagrass as carbon storage are still very rare or limited. This study was aimed to estimate carbon storage on seagrass community  in Marine Nature Tourism Park of Kotania Bay Area, Western  Seram,  Maluku Province. The  quadrat transect method of 0.25 m2 for each plot was used to collect seagrass existence. The content of carbon in the sample of dry biomass of seagrass was analyzed in the laboratory using Walkley & Black method. The results  showed that total carbon stored was higher in both Osi and Burung Islands of Kotania Bay  than other studied areas (Buntal and  Tatumbu Islands, Marsegu Island, Barnusang Peninsula, Loupessy and  Tamanjaya Village).    The average  carbon stored in  Kotania Bay waters was 2.385 Mg C ha-1,  whereas the total of carbon stored was 2054.4967 Mg C.